Chest surgery - Dienemann, Hendrik; Hoffmann, Hans; Detterbeck, Frank (Springer, 2015)
Chest Surgery provides readers with a comprehensive and authoritative text that explains and illustrates all thoracic surgery procedures, with the exception of those on the heart and esophagus. The easy-to-read text is supported by clear, instructive line drawings and intraoperative photographs. The result is a well-illustrated practical guide for the seasoned and novice practitioner alike. The contributors, who are all acknowledged experts, demonstrate simple and safe forms of operation by distilling their experience into the most efficient methods for both standard and less common procedures. Each chapter is framed by a short introduction and a conclusion covering relevant aspects in epidemiology, historical information, pathophysiology, patient care, and outcome data, as well as the latest key references. For ease in following a surgical procedure, the text description of each step is coupled with an appropriate drawing. Bearing in mind that there are often numerous ways of performing an operation, the surgical trainee should first of all recognize the basic principles underlying all surgery. This book takes care to impart those principles. It will be the "must-have" guide for all thoracic surgery residents who wish to acquaint themselves with the latest developments in this constantly expanding field
Hier auch später erschienene, unveränderte Nachdrucke
Keywords: Atlas; Aufsatzsammlung; Thoraxchirurgie